1993
DOI: 10.1051/agro:19930502
|View full text |Cite
|
Sign up to set email alerts
|

Influence de la recombinaison sur la variabilité génétique. II. Étude par simulations

Abstract: complement an experimental study of the possible interest for plant breeders of an allele increasing recombination rates. In the first simulation study, 4 populations of 10 individuals were simulated in the case of high (45%), medium (19.6%) and low (6.9%) recombination frequencies. Ten-plant populations were derived by one generation, either from selfing or from crossing in a circular mating design, from each of the 4 populations. For each initial population, the distribution of the genetic variances in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
(6 reference statements)
0
1
0
1
Order By: Relevance
“…Since breeding is a numbers game, this would require populations that are too large. Theory demonstrated that a two or more step procedure is much more efficient although slightly slower (Kervella et al [ 1993 ]). Recurrent selection with a male sterility gene to facilitate intercrossing will be a way to go (Grenier et al unpublished work).…”
Section: Reviewmentioning
confidence: 99%
“…Since breeding is a numbers game, this would require populations that are too large. Theory demonstrated that a two or more step procedure is much more efficient although slightly slower (Kervella et al [ 1993 ]). Recurrent selection with a male sterility gene to facilitate intercrossing will be a way to go (Grenier et al unpublished work).…”
Section: Reviewmentioning
confidence: 99%
“…Dans cette expérience, le gène Rm1 qui accroît les taux de recombinaison dans la plupart des segments testés, excepté le segment sur le chromosome IV délimité par les gènes B1 et An6 (Farcy et al, 1986;Cornu et al, 1989;Robert et al, 1991) (Miller et Rawling, 1967;Mather et Jinks, 1971;Gallais, 1974, Snape, 1976Snape et Simpson, 1981 (Kervella et al, 1993).…”
Section: Introductionunclassified